Women, Wars, and Subaltern Memories from the Philippines to Galicia: (Dis)Affections in Merlinda Bobis and Simón Casal - Núñez-Puente, Carolina (Madrygal. Revista de Estudios Gallegos, 2020)
This article compares two cultural creations, “Fish-hair woman” (1999) –a story by the Filipina- Australian author Merlinda Bobis– and Lobos sucios (2015) –a film by the Galician director Simón Casal de Miguel, both inspired by real events. My principal aim is to analyze the representation of women in war times, as they rarely go down in history; therefore, I consider my objects of study as examples of subaltern memories (e.g. Traverso 2007) that can intervene in historical discourse. My critical perspective is interdisciplinary, including studies on gender violence (e.g. Sanford, Stefatos, and Salvi 2016), historical memory (e.g. Yusta 2018), affect theory (e.g. Ahmed 2004), and feminism (e.g. Garcia 2018). Despite the geographical distance between the scenarios of Lobos sucios and “Fish-hair woman”, the protagonists show that rural women have enough talent and leadership skills to carry out decisive actions in both the private and public domains. Many of the topics developed in both oeuvres also coincide: violence against women multiplies during armed struggles (e.g. sexual abuse, torture), while they cope to survive and even rebel against injustices; nature, in particular the river, is portrayed as an agent of assistance to the victims of battles; care and the supernatural are linked to the rural woman beyond patriarchal parameters; finally, intersubjective love, especially between people of different cultures (i.e. a Filipina and a male Australian, a Galician woman and a Belgian man), is revealed as a powerful force to combat war horror. Bobis and Casal make sophisticated use of formal resources (e.g. magic realism, symbolism) that invites the public to enter into the atmosphere of their plots and reflect on them. Besides denouncing gender violence in armed conflicts, Bobis and Casal show that rural women’s lives –their courage, resilience, and solidarity– are far from the patriarchal stereotype, deserving to be revised in depth.
Keywords: Merlinda Bobis; Simón Casal de Miguel; Gender; Social Class; War; Subaltern Memories; Affect Theory; Feminism